Inflammatory myofibroblastic tumor of abdomen: Computerized tomographic (CT) and pathological findings - Wichchuda Yamrubboon (2018)
Inflammatory Myofibroblastic Tumor (IMT) is the recent name of Inflammatory pseudotumor which was in intermediate group of fibrous-origin tumor. The authors retrospectively reviewed such cases in Ramathibodi Hospital from January 2001 to December 2005. There were 115 cases of fibrous-origin tumor, which was IMT in 17 cases. Nine cases occurred in the abdomen and only 3 of these had complete computerized tomographic (CT) imaging. One was hypodense liver mass with thick rim enhancement. Another one in the liver presented as a liver abscess which appeared as multiloculated hypodense mass with enhanced septum. The third case was a large malignant-looking retroperitoneal mass and having a small accompanying hepatic lesion which rapidly grew in the follow up study at nine months. IMT in the abdomen was scanty. The diagnosis was done with difficulty because of different signs and symptoms such as fever and palpable abdominal mass. The laboratory findings were nonspecific or within normal limits. Tissue biopsy was the way of definite diagnosis. We reported 3 cases of abdominal IMT with variable imaging findings that may lead to inappropriate treatment. Recognization of such findings will help achieve correct diagnosis.